Overall survival with cisplatin-gemcitabine and bevacizumab or placebo as first-line therapy for nonsquamous non-small-cell lung cancer: results from a randomised phase III trial (AVAiL) - Reck, M; von Pawel, J; Zatloukal, P; Ramlau, R; Gorbounova, V; Hirsh, V; Leighl, N; Mezger, J; Archer, V; Moore, N; Manegold, C; BO17704 Study Group (Annals of oncology, 2010)
BACKGROUND: Bevacizumab, the anti-vascular endothelial growth factor agent, provides clinical benefit when combined with platinum-based chemotherapy in first-line advanced non-small-cell lung cancer. We report the final overall survival (OS) analysis from the phase III AVAiL trial. PATIENTS AND METHODS: Patients (n = 1043) received cisplatin 80 mg/m(2) and gemcitabine 1250 mg/m(2) for up to six cycles plus bevacizumab 7.5 mg/kg (n = 345), bevacizumab 15 mg/kg (n = 351) or placebo (n = 347) every 3 weeks until progression. Primary end point was progression-free survival (PFS); OS was a secondary end point. RESULTS: Significant PFS prolongation with bevacizumab compared with placebo was maintained with longer follow-up {hazard ratio (HR) [95% confidence interval (CI)] 0.75 (0.64-0.87), P = 0.0003 and 0.85 (0.73-1.00), P = 0.0456} for the 7.5 and 15 mg/kg groups, respectively. Median OS was >13 months in all treatment groups; nevertheless, OS was not significantly increased with bevacizumab [HR (95% CI) 0.93 (0.78-1.11), P = 0.420 and 1.03 (0.86-1.23), P = 0.761] for the 7.5 and 15 mg/kg groups, respectively, versus placebo. Most patients ( approximately 62%) received multiple lines of poststudy treatment. Updated safety results are consistent with those previously reported. CONCLUSIONS: Final analysis of AVAiL confirms the efficacy of bevacizumab when combined with cisplatin-gemcitabine. The PFS benefit did not translate into a significant OS benefit, possibly due to high use of efficacious second-line therapies.
Keywords: placebo; Gemcitabine; adenoskvamózní karcinom; Carcinoma, Adenosquamous; Prognosis; Deoxycytidine; monoklonální protilátky; nádory plic; Antibodies, Monoclonal; Neoplasm Recurrence, Local; míra přežití; lokální recidiva nádoru; bevacizumab; Neoplasm Staging; nemalobuněčný karcinom plic; prognóza; Placebos; Humans; deoxycytidin; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; Survival Rate; Carcinoma, Non-Small-Cell Lung; Antineoplastic Combined Chemotherapy Protocols; gemcitabin; staging nádorů; protokoly protinádorové kombinované chemoterapie; Lung Neoplasms; lidé; Bevacizumab